The effect of treatment sessions to raise the level of motivation for patients with a complete rupture of the cruciate ligament (Journal of the College of Basic Education, 2022)
The research included five chaptersThe aim of the study is to raise the level of motivation among athletes with complete severing of the anterior cruciate ligament, on a research sample of (5) injured athletes from the second degree from various local clubs. The experiment was conducted in the sports rehabilitation hall of the Directorate of Sports Medicine, from the period 9/ 2/2014 until 3/20/2014, and the experimental method was used for the research and the motivation scale was used to measure the research variable, and after completing the experiment, the program (spss) was used to extract the results,